PREVALENCE AND DETERMINANTS OF PREHYPERTENSION AND HYPERTENSION AMONG ADOLESCENTS IN THIRUVALLUR DISTRICT, TAMIL NADU, INDIA: A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hypertension, once considered predominantly a disease of adulthood, is increasingly recognized among adolescents, particularly in settings where non-communicable diseases may remain underdiagnosed. Early identification of elevated blood pressure is essential to prevent future cardiovascular morbidity and mortality. Objectives: To determine the prevalence of elevated blood pressure and hypertension among adolescents aged 10–19 years attending the Rural Health Training Centres in Thiruvallur district, Tamil Nadu, and to identify socio-demographic, behavioural, and clinical factors associated with elevated blood pressure. Methods: An analytical cross-sectional study was conducted among 240 adolescents from June to December 2025. Participants were recruited using convenience sampling. Data were collected using a semi-structured, pre-tested questionnaire. Blood pressure was measured and classified according to the 2017 American Academy of Pediatrics (AAP) Clinical Practice Guideline. The chi-square test was used to assess associations, and multivariable logistic regression analysis was performed to identify independent predictors of elevated blood pressure. Results: Elevated blood pressure (Prehypertension), Stage 1 hypertension, and Stage 2 hypertension were observed in 3.8%, 2.9%, and 5.0% of participants, respectively, with an overall hypertension prevalence of 7.9%. Male sex (p = 0.03), family history of hypertension (p = 0.01), and overweight status (p = 0.001) were significantly associated with elevated blood pressure. Multivariable logistic regression identified male sex (AOR 2.4, 95% CI 1.1–5.3), family history of hypertension (AOR 2.9, 95% CI 1.3–6.4), and overweight status (AOR 3.8, 95% CI 1.7–8.6) as independent predictors. Physical activity, screen time, dietary habits, and sleep duration were not significantly associated with elevated blood pressure. Conclusion: Elevated blood pressure and hypertension represent important health concerns among adolescents, with male sex, family history of hypertension, and overweight identified as key determinants. Routine blood pressure screening, targeted health education, and lifestyle interventions should be integrated into adolescent health programmes to facilitate early detection and reduce the future burden of cardiovascular disease.